Inefficient Short-Time Work - Pierre Cahuc; Sandra Nevoux (Institute of Labor Economics (IZA), 2017)
This paper shows that the reforms which expanded short-time work in France after the great 2008-2009 recession were largely to the benefit of large firms which are recurrent short-time work users. We argue that this expansion of short-time work is an inefficient way to provide insurance to workers, as it entails cross-subsidies which reduce aggregate production. An efficient policy should provide unemployment insurance benefits funded by experience rated employers' contributions instead of short-time work benefits. We find that short-time work entails significant production losses compared to an unemployment insurance scheme with experience rating.
Keywords: J63; J65; 330; short-time work; unemployment insurance; experience rating